2021
DOI: 10.3390/nu13041057
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Inflammatory Markers in Children with Cow’s Milk Allergy Treated with a Milk-Free Diet

Abstract: Background: The aim of the study was to establish whether the use of a strict milk-free diet in children with cow’s milk allergy, resulting in the resolution of clinical symptoms of the disease, also extinguishes the inflammatory reaction induced by the allergy. Methods: We examined 64 children (aged 3–6 years) with a diagnosed cow’s milk allergy who had been treated with an elimination diet for at least six months and showed remission of the disease’s clinical symptoms as a result of the treatment. The contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
0
5
0
1
Order By: Relevance
“…The review concluded that no sufficient evidence could confirm the value of FC in CMPA, which may be due to the small size and different people. There were three additional studies that reported contradictory results on FC levels in CMPA patients this year [10,16,17]. Qiu et al [17] conducted a prospective case-control trial and found a significantly higher FC level in the milk-allergic infants than in the nonallergic group IgE (median: 410 vs. 141 μg/g, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The review concluded that no sufficient evidence could confirm the value of FC in CMPA, which may be due to the small size and different people. There were three additional studies that reported contradictory results on FC levels in CMPA patients this year [10,16,17]. Qiu et al [17] conducted a prospective case-control trial and found a significantly higher FC level in the milk-allergic infants than in the nonallergic group IgE (median: 410 vs. 141 μg/g, p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Nineteen pieces of literature were selected for full-text revision, 7 of those were also excluded with no complete information. Finally, 12 pieces of literature were included in the meta-analysis [4,7,8,[10][11][12][13][14][15][16][17][18].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because cow milk allergy in young children has gastrointestinal inflammatory manifestations including enteropathy, increased inflammatory cell infiltration, and cytotoxic expression [ [33] , [34] , [35] ]. Cow milk allergy is also associated with elevated fecal calprotectin concentrations [ [36] , [37] , [38] ] and has been linked with higher risk of type 1 diabetes [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…Сходство симптоматики и сочетание патогенетических механизмов затрудняет её диагностику. В подобных случаях ис-пользуют методы определения маркеров аллергического воспаления, а также вспомогательные методы выявления аллергической гиперчувствительности к пищевым продуктам [61].…”
Section: диагностикаunclassified